DNA extraction and PCR optimization for DNA barcode analysis of commercially-grown coffee varieties in Nepal - Pokharel, Shreejan; Khanal, Bignya Chandra; Basnet, Anish; Pandey, Gyanu Raj; Basnet, Samsher (Kathmandu University Journal of Science Engineering and Technology, 2023)
The isolation of high-quality genomic DNA is an essential criterion for further molecular analysis. Coffea genus is well known for its high amount of polyphenols, polysaccharides, and other secondary metabolites that degrades the quality of the DNA isolation needed for further down streaming processes. The present work was carried out to obtain a simple and efficient DNA isolation protocol generating high-quality amplification for barcoding. The protocol involves modifying the CTAB extraction, incorporating the use of polyvinylpyrrolidone and β -mercaptoethanol yielding quality DNA with a ratio (A260/280) between 1.8–2.0 indicating low contamination. The PCR conditions were optimized for high amplification based on the optimal concentration of MgCl2 (3 mM), primer (0.5 µM), Taq polymerase (0.2 U), 50–60 ng of DNA template, and cycle conditions as initial denaturation of 94○C for 4 min followed by 35 cycles of denaturation at 94○C for 50 sec, annealing (respective of barcodes) for 50 sec and extension at 72○C for 80 sec, followed by a final extension at 72○C for 7 min. The optimal conditions produced highly amplified reproducible data. Thus, the optimized method proposed enabled a simple DNA extraction and PCR amplification for Coffea genus and may serve as an efficient tool for further molecular analysis.